PKM Pemanfaatan Limbah Plastik Menjadi Furniture Rumah Tangga Pada Istri-Istri Pemulung - Megavitry, Rissa; Irmayanti, Irmayanti; NFH, Alifya (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Ecobrick innovation becomes household furniture as an effort to tackle plastic waste and increase the income of scavenger wives. Antang Final Disposal Site (TPA) is one of the locations that has the potential for plastic waste pollution. Many efforts have been made to overcome over capacity in the Antang TPA, but until now the problem of waste accumulation has not been completely resolved. This Community Service activity aims to overcome the pile of garbage in the Antang TPA while increasing the productivity of the community, especially the scavenger's wives who only expect income from their husbands. Data collection methods were carried out through discussions, surveys, partner determination, pretest, training evaluation, direct practice of making ecobrick which were then innovated into household furniture, monitoring and posttest. The results of this training increased partners' understanding of ecobrick and how to manage waste into something useful by 100%, 91.67% of partners knew about making ecobrick, 83.33% of partners agreed to form entrepreneurship from the results of making ecobrick into household furniture. The training program for the use of plastic waste into a visionary innovation product in the form of household furniture with the ecobrick technique still needs sustainability training for more diverse products so that it can increase the quantity of products produced.